EFL STUDENTS’ PERCEPTIONS OF USING YOUTUBE VIDEOS FOR VOCABULARY MASTERY - H, Khairuddin; Sofyan, Ryan Rayhana; Radhiyani, Fitri (Universitas Negeri Makassar, 2025)
This study explores EFL students’ perceptions of using YouTube as a tool for learning English vocabulary. Using a qualitative case study involving ten sixth-semester students from Universitas Negeri Makassar, the research investigates how students engage with YouTube to develop vocabulary. The findings show that students generally perceive YouTube as an effective learning medium due to its audiovisual nature, real-world context, and interactive content. Students reported that YouTube enables them to discover, understand, and evaluate vocabulary in authentic situations. However, issues like inaccurate subtitles and fast-paced speech were also noted. The study concludes that YouTube, when used selectively and purposefully, enhances students’ motivation and vocabulary comprehension.